WOMAN AND MAN’S SPEECH STYLE USED BY THE MAIN CHARACTERS IN LOL (LAUGHING OUT LOUD) MOVIE - PUSPITASARI, RATIH (Jurnal Ilmiah Mahasiswa FIB, 2013)
Language is important for the society because it is part of human life. In common communication, a person may use a certain code or variety that is called as style. The style which occurs in spoken discourse is called as speech style. Speech styles are the characteristics mode arranging the words, particularly the use of language between male and female. In this study, the writer is interested in investigating the differences between woman and man which is reflected in LOL movie. The research problems of this study are (1) What are the speech style used by the female main characters in LOL movie?; (2) What are the speech style used by the male main characters in LOL movie? This study used descriptive qualitative approach. The data were the conversations between the female and male main characters. In analyzing the data, the writer used gender differentiation theory proposed by Adelaide Haas (1979, p.616). It is stated that male speech and female speech style have been observed to differ in their form, topic, content, and use. The finding shows that both women and men have differences in the way of speaking. Based on form, female characters tend to swear and use more slang words while man character does not show it. Based on the topic, women are likely to talk about life’s trouble, pornography, and life style. The topic that man builds in this movie is also the life trouble. The content of the conversation of this movie supports the theory that woman has positive value judgment and man has hostile judgment. Based on use, women are assertive while men are nonassertive. In conclusion, based on Adelaide Haas’ theory, the writer found out that women and men language are mostly different. It happened because women like to maintain the relationship between each other while men like to say what they want to say. Keywords: speech style, language and gender, woman and man’s language